2018
DOI: 10.17219/dmp/99072
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fruit and vegetables intake in periodontal diseases: A systematic review

Abstract: Periodontal diseases affect up to 90% of the population worldwide. Deficiencies in vitamins, minerals and polyphenolic compounds, whose main sources are fruit and vegetables (F&V), may predispose to these diseases. The PICO (Patient, Intervention of interest, Comparison or Control Intervention, and Outcome) question was: What is the effect of F&V intake on the outcomes of periodontal diseases, observed in either experimental or observational studies of human populations suffering from periodontitis or gingivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
(99 reference statements)
1
9
0
Order By: Relevance
“…The main finding of this study was that a poor‐quality diet was associated with periodontal pocket formation during the 11‐year follow‐up period. This is in line with earlier studies where the progression of disease has been examined in relation to food groups or a combination of nutrients either alone or combined with periodontal treatment . For example, in a study performed among 70‐year‐old people, dark green and yellow vegetables were inversely associated and cereals, nuts and seeds, sugar, sweeteners and confectioneries were positively associated with periodontal disease events during a 6‐year follow‐up.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The main finding of this study was that a poor‐quality diet was associated with periodontal pocket formation during the 11‐year follow‐up period. This is in line with earlier studies where the progression of disease has been examined in relation to food groups or a combination of nutrients either alone or combined with periodontal treatment . For example, in a study performed among 70‐year‐old people, dark green and yellow vegetables were inversely associated and cereals, nuts and seeds, sugar, sweeteners and confectioneries were positively associated with periodontal disease events during a 6‐year follow‐up.…”
Section: Discussionsupporting
confidence: 88%
“…This is in line with earlier studies where the progression of disease has been examined in relation to food groups or a combination of nutrients either alone or combined with periodontal treatment. 29 For example, in a study performed among 70-year-old people, 30 dark green and yellow vegetables were inversely associated and cereals, nuts and seeds, sugar, sweeteners and confectioneries were positively associated with periodontal disease events during a 6-year follow-up. In another study, 31 the consumption of fruits and vegetables and the intake of β-carotene, vitamin C, α-tocopherol, eicosapentaenoic acid and docosahexaenoic acid were associated with enhanced periodontal healing after scaling and root planing in a group of 34-to 90-year-old nonsmokers with chronic periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Besides polyphenols, other phytochemicals, including vitamin C (ascorbic acid), vitamin E (␣-tocopherol), vitamin A, ␤-carotene, and coenzyme Q-10, and minerals provided by fruits, vegetables, nuts, and whole grains in the MD are effective for maintaining periodontal homeostasis (50)(51)(52)(53). Indeed, Skoczek-Rubiń ska and colleagues (54) found that the consumption of at least 5 servings of fruits and vegetables per day may prevent the progression of periodontal diseases. Accordingly, in our intervention, species-level OTUs annotated as periodontopathogenic bacteria were found to be anticorrelated with dietary fiber intake and to the Mediterranean diet adherence score.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis patients need continuous professional care including behavioural support to reduce the harmful impact of both aetiological causes and risk factors. Current evidence from clinical studies reveal that smoking cessation (Leite et al, 2018), diabetes control (Botero, Rodriguez, & Agudelo-Suarez, 2016; Kapellas et al, 2017), increase in physical activity (Ferreira et al, 2019), dietary adjustments (Skoczek-Rubinska, Bajerska, & Menclewicz, 2018;Van der Velden, Kuzmanova, & Chapple, 2011) and weight loss (Weyant et al, 2004) improve periodontal health and the patients' quality of life. Therefore, periodontal care providers have a key role to play in supporting their patients' health behaviour and thus face the challenge to adopt interventions for the promotion of health behaviour change specifically through interventions for smoking cessation, diabetes control, increase in physical exercise (activity), change of diet, carbohydrate (dietary sugar) reduction or weight loss.…”
Section: S Y S T E M a T I C R E V I E Wmentioning
confidence: 99%